Implementation of BMB3 in the Implementation of Guidance and Counseling Service Management in Educational Institutions - Torly Amora Jofipasi; Neviyarni S; Yarmis Sukur; Jon Efendi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Based on Law no. 20/2003, article 1 paragraph (1),